Transformasi Digital Sebagai Pemicu Disintegrasi Keluarga (Dampak Judi Online di Kabupaten Sambas) - Aidil; Sabari; Halim Setiawan (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
Globalization and digitalization bring both positive and negative impacts. The positive impacts of digital transformation include facilitating access to information, supporting business activities, and various other conveniences. However, one of the negative impacts of digital transformation is the occurrence of family disintegration. This study aims to examine two aspects: (1) the impact of family disintegration caused by online gambling in Sambas Regency, and (2) the Qur’anic perspective on the impacts of online gambling in Sambas Regency. This research employs a qualitative approach with a phenomenological research design. Data were collected through observation, interviews, and documentation. Primary data were obtained from the Religious Court of Sambas Regency, while secondary data consisted of journal articles, electronic media sources, and other relevant materials related to the research topic. Data analysis in this study follows the interactive model of Miles and Huberman, which includes data collection, data condensation (data reduction), data display, and conclusion drawing and verification. Meanwhile, data trustworthiness was ensured using the trustworthiness criteria proposed by Lincoln and Guba, namely credibility, transferability, dependability, and confirmability. The findings indicate that (1) the disintegration resulting from online gambling significantly affects the social, economic, and psychological aspects of family life, and (2) from the Qur’anic perspective, online gambling damages faith, harmony, and family resilience.